A case-control study of influenza vaccine effectiveness among Malaysian pilgrims attending the Haj in Saudi Arabia - Mustafa, Amal Nasir; Abdullah, Nasuruddi; Bradford D, Gessner; Raman, Ismail; Yusoff, Ahmad Faudzi; Ishak, Ilina; Mohd Ismail , Merican (Elsevier, 2003)
Objectives: To determine influenza vaccine effectiveness against clinically defined influenza-like illness among Malaysian pilgrims attending the Haj in Saudi Arabia.